Self-efficacy and green entrepreneurship - Tan K.L.; Suhaida S.; Leong Y.P. (Institute of Physics Publishing, 2023)
The objective of this study is to investigate empirically the extent to which self-efficacy contributes to the development of green entrepreneurial intention. The measurement constructs of self-efficacy were classified into market opportunities, innovative environment, initiating relationships, defining purpose, coping with challenges, and developing human resources. The study comprises 252 usable convenient samples through structured questionnaires. The coefficient of determination R2 shows that the variance of intention to entrepreneurship is explained by the variance of the independent variables. It was also found that the model is fit for prediction. Published under licence by IOP Publishing Ltd.